Leprosy control: perspectives & epidemiological and operational aspects - Gonçalves, Aguinaldo; Mantellini, Glauca G.; Padovani, Carlos Roberto [UNESP] (Instituto de Medicina Tropical, 2010)
OBJETIVOS: A partir de acervo de 200 textos acadêmicos e de documentos de organismos nacionais e internacionais voltados ao controle da hanseníase publicados no período de 1999 a 2008, procurou-se estudar respectivas possibilidades evolutivas futuras, empregando-se os subsídios do recurso de análise de cenários. MÉTODOS: A reconstrução metodológica adotada foi de natureza qualitativa, fulcrada nas técnicas de revisão bibliográfica e análise de conteúdo. Esta última foi empregada na tipificação documental categorial frequencial contigencial, de acordo com devida fundamentação pertinente. RESULTADOS: Recuperaram-se elementos atuais importantes de natureza epidemiológica e operacional, bem como de respectivas perspectivas. CONCLUSÕES: Projeta-se que a manutenção dos coeficientes de incidência da doença coloca reptos econômicos e sanitários a desafiar desde o modelo neoliberal de organização societária mundial até competências específicas das ações das equipes de saúde em campo.

OBJECTIVES: As a starting point, a vast variety of 200 technical papers and documents published during the ten years 1999-2008, from Brazilian and international organizations dedicated to the control of leprosy, was taken. A study was then undertaken to investigate its future evolutive possibilities by employing resources obtained from scenario analyses. DESIGN: The methodological reconstruction in use was of a qualitative nature, based on a bibliographic review and content analysis techniques. The latter were employed in a documental, categorical, contingent, frequency-based format, in compliance with appropriate and pertinent conditions. RESULTS: Nowadays, important elements on epidemiological and operational aspects have been regained, as well as respective perspectives. CONCLUSIONS: A projection is made towards the fact that the maintenance of the disease's present incidence levels constitute economic and sanitary challenges that confront issues ranging from the neoliberal model of global societal organization to specific competences of actions taken by health teams in the field.
Controle da hanseníase: perspectivas e aspectos epidemiológicos e operacionais
Keywords: Leprosy; Control; Epidemiology